Process evaluation of a Germany-wide complex intervention to prevent dysregulated screen time in under threes: a RE-AIM-approach - Schemmer, Juliane; Martin, David; Krafft, Hanno; Maurer, Tobias; Emgenbroich, Anke; Monks, Sean; Schwarz, Silke (Frontiers in Pediatrics, 2025)
BackgroundChildren's current screen time is well above current recommendations and is associated with many health consequences in the first years of life.MethodsThe complex intervention study “Screen free till 3” introduced parent education to a regular examination of 6-month-old children in outpatient pediatric practices. Pediatric practices were cluster-randomized in a 2:1 ratio (intervention group:control group). 2,581 pediatric practices received the intervention materials by cold call and participated by self-selection. The study includes a process evaluation that examines the implementation process. In this article, four different quantitative methods of the process evaluation are evaluated according to the RE-AIM scheme.Result33.4% of pediatric practices confirmed their participation in the study. 10,391 parents took part in the pre-interventional app-based parent survey. 151 interested institutions contacted the research team by email. The majority (84.1%) asked to take part in the study. 518 pediatric practices took part in a telephone survey, of which 87.2% said that they are supported by the intervention materials and 91.6% would recommend the project to others.DiscussionThe RE-AIM analysis shows a high reach of parents via the app. The high adoption by pediatric practices and other institutions characterizes the relevance of the topic as well as the innovation of the study materials. After one and a half years, the intervention is firmly integrated into the structures of pediatric practices in Germany.Trial register numberhttps://drks.de/search/en/trial/DRKS00032258, DRKS00032258.